Hubungan pengetahuan dan sikap keluarga dengan perawatan anggota keluarga yang menderita asam urat - Hernanda, Rice; Masruroh, Siti (JOURNAL OF Community Health Issues, 2024)
Background: Gouty arthritis is a substance resulting from purine metabolism which is normally excreted in the urine. According to WHO, the prevalence of gout arthritis in the world is 34.2% and the prevalence in Lampung Province is 23,352. High uric acid levels can cause severe joint pain. The external factors that influence high uric acid levels are family knowledge and attitudes which can influence a person's response to the causes and treatment of illnesses and diseases suffered and influence achieving optimal health. Purpose: To determine the relationship between family knowledge and attitudes and the care of family members suffering from gout. Method: Quantitative research with analytical survey research design and cross sectional approach. The object of the research is the knowledge and attitudes of families regarding the care of family members who suffer from gout. The research subjects were families of gout patients in the working area of ​​the Waylima Inner City Health Center. The number of samples in the research was 95 respondents. The method used for sampling was the random sampling method. This research uses the chi square statistical test. Results: The research obtained results from 95 respondents, it was found that the highest knowledge was 41 respondents (43.2%) in the sufficient category, the highest attitude was 60 respondents (63.2%) in the positive category and the highest care for family members was 48 respondents (50.5%) in the sufficient category and the statistical results of the Chi square test Conclusion: There is a significant relationship between knowledge and caring for family members with a p-value of 0.003 and family attitudes and caring for family members suffering from gout with a p-value = 0.001. Keywords: Attitude; Family Member Care; Gout Atritis; Knowledge Pendahuluan: Arthritis gout merupakan suatu zat hasil metabolisme purin yang normalnya dibuang melalui urin. Menurut WHO Prevalensi gout arthritis di dunia sebanyak 34,2% dan prevelansi Provinsi Lampung 23.352. Kadar asam urat yang tinggi dapat menyebabkan nyeri sendi hebat. Adapun faktor eksternal yang mempengaruhi kadar asam urat tinggi yaitu pengetahuan dan sikap keluarga yang dimana dapat mempengaruhi respon seseorang tentang penyebab serta penanganan terhadap sakit dan penyakit yang diderita serta mempengaruhi dalam mencapai derajat kesehatan yang optimal. Tujuan: Untuk mengetahui hubungan pengetahuan dan sikap keluarga dengan perawatan anggota keluarga yang menderita asam urat. Metode: Penelitian kuantitatif dengan desain penelitian survey analitik dan pendekatan cross sectional. Objek penelitiannya adalah pengetahuan dan sikap keluarga dengan perawatan anggota keluarga yang menderita asam urat. Subyek penelitiannya adalah keluarga pasien asam urat di wilayah kerja Puskesmas Kota Dalam Waylima. Jumlah sampel dalam penelitian adalah sebanyak 95 responden. Metode yang digunakan untuk pengambilan sampel dengan menggunakan metode random sampling. Penelitian ini menggunakan uji stastitik chi square. Hasil: Penelitian memperoleh hasil dari 95 responden didapatkan pengetahuan tertinggi sebanyak 41 responden (43.2%) pada kategori cukup, sikap tertinggi sebanyak 60 responden (63.2%) pada kategori positif dan perawatan anggota keluarga tertinggi sebanyak 48 responden (50.5%) pada kategori cukup dan hasil statistik uji Chi square Simpulan: Adanya hubungan yang signifikan antara pengetahuan dengan perawatan anggota keluarga dengan nilai p-value 0,003 dan sikap keluarga dengan perawatan anggota keluarga yang menderita asam urat dengan nilai p-value = 0,001. Kata Kunci : Gout Atritis; Pengetahuan; Sikap; Perawatan Anggota Keluarga